Control coordination abilities in shock combat sports - Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2014)
Purpose: optimize the process control level of coordination abilities in martial arts. Material and Methods: analysis and compilation of scientific and methodological literature, interviews with coaches of drum martial arts, video analysis techniques, teacher observations. Results: identified specific types of coordination abilities in shock combat sports. Pod branny and offered specific and nonspecific tests to monitor the level of species athletes coordination abilities. Conclusion: it is determined that in order to achieve victory in the fight martial artists to navigate the space to be able to assess and manage dynamic and spatio-temporal parameters of movements, maintain balance, have a high coordination of movements. The proposed tests to monitor species coordination abilities athletes allow an objective assessment of not only the overall level of coordination, and the level of specific types of manifestations of this ability.